KONSEP DIRI PENYANDANG ALBINO DI PROVINSI RIAU - Fauzi "; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Every human being hopes for a normal physical condition from birth, but in reality, the physical limitations of an individual cannot be avoided, being born with an albino that does not have pigments to the skin, eyes, hair and all hair on the body makes albino people feel different from people in general, not only were they ostracized, they also had a discrimination experience that made them feel ashamed, angry and inferior.The purpose of this study was to determine the physiological aspects, psychological aspects, psycho-sociological aspects and experience of communication with albino persons in Riau Province. This study uses qualitative research methods with a phenomenological approach. The research subjects consisted of five albino people in Riau Province who were selected using exsidental techniques. This study uses data collection techniques of observation, interviews and research documentation.The results of this study indicate that people with albino in Riau Province when viewed from the physiological aspects of people with albino differ from people in general, not only different physical appearance but also have a weak body resistance. Judging from the psychological aspects of people with albino tend to have their own sadness in seeing themselves as people who are unhappy, pessimistic, unable to control themselves and feel inferior. When viewed from the psycho-sociological aspects, people with albino begin to accept the situation and communicate with the community even though there are those who choose to close themselves to avoid people's questions, and if seen from the experience of communication with albino people in Riau Province, they tend to have unpleasant communication experiences. one eye because of its physical appearance, but the pleasant communication experience experienced by albino people is seen as hardworking, friendly and socializing.Keyword:Albino people, Self-Concept, Riau Province